Teacher strategies for managing disruptive behavior and student preferences: A case study in primary education - Anang Ma'ruf; Ferdiansyah Ferdiansyah; Sukrin Sukrin; Tasrif Tasrif (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2026)
Disruptive behavior in elementary classrooms can interfere with learning processes, classroom interaction, and students’ emotional comfort during learning activities. Previous studies have largely focused on teachers’ perspectives in managing disruptive behavior, while students’ preferences toward teacher strategies remain underexplored. This study aimed to examine teachers’ strategies in managing disruptive behavior and explore students’ preferences toward those strategies in elementary school classrooms. This study employed an exploratory qualitative case study design involving 15 participants consisting of five elementary school teachers and ten students (Male = 9, Female = 6). Participants were selected purposively based on their direct experiences with disruptive classroom behavior and classroom management practices. Data were collected through semi-structured interviews and classroom observations and analyzed using thematic analysis. The findings revealed that teachers applied various strategies, including interactive learning, individual and empathetic approaches, behavior management, understanding students’ characteristics, and teaching social skills. Students generally preferred supportive, interactive, and emotionally safe classroom environments that encouraged participation and positive teacher–student relationships. The findings further showed that disruptive behavior was often related to boredom, emotional discomfort, and passive learning situations rather than merely intentional misconduct. From the perspective of Islamic education, classroom management was closely associated with the cultivation of adab, empathy, patience, and respectful social interaction. These findings indicate the importance of shifting from reactive disciplinary approaches toward more student-centered, emotionally supportive, and relationship-based classroom management practices to preventatively reduce disruptive behavior in elementary education.